ANALISIS PRIORITAS PENINGKATAN KUALITAS PENGALAMAN PENGGUNA E-CASH MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE DAN IMPORTANCE-PERFORMANCE ANALYSIS - Muhammad Fajri Karbila; Lutfi Firmana; I Gede Ari Kusuma Atmaja; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (LPPM Universitas Abdurrab, 2026)
This research aims to analyze the quality of User Experience (UX) and determine the priority for improvement in the digital payment system (E-Cash) at Yayasan Al-Halim Garut. The primary problem underlying this study is the need for sistem optimization to better align with user needs in a school environment. The research method employed is a quantitative approach integrating the User Experience Questionnaire (UEQ) and Importance-Performance Analysis (IPA). Data were collected through a survey of 60 active E-Cash users. The results indicate that the E-Cash sistem has a performance suitability level of 85%, falling into the high category, despite an average gap value of -0.70. Through IPA mapping, it is concluded that the top priority for improvement lies in four indicators within Quadrant I, specifically regarding sistem friendliness and support for user activities. Meanwhile, the novelty and modernity aspects of the sistem in Quadrant II are identified as strengths that must be maintained. This research provides strategic recommendations for managers to focus development on aspects of system friendliness and support for user activities, so that it is expected to increase the level of performance conformity > 85% and the gap value > 0 in the next evaluation cycle.